دراسة تحليلية لواقع الاستثمار في المدن الصناعية السورية خلال الفترة 2004-2012. - محمود حبيب; أسعد الحارث (Latakia University Journal - Economic and Legal Sciences Series, 2017)
هدفت هذه الدراسة إلى التعرف على المدن الصناعية الأربع في الجمهورية العربية السورية، ومعرفة حجم النفقات والإيرادات لهذه المدن، بالإضافة إلى معرفة عدد المشاريع المخصصة والمنفذة والمشملة في هذه المدن، وتوزيع المقاسم بين أنواع الصناعات المختلفة، بالإضافة إلى دراسة العلاقة الارتباطية بين العديد من متغيرات الدراسة. استخدم الباحث المنهج الوصفي التحليلي. كما تم دراسة و تحليل البيانات باستخدام برنامج spss ، وبعد تحليل البيانات تبين انخفاض عدد المشاريع المنفذة، عدم وجود علاقة ارتباطية بين معظم متغيرات الدراسة، عدم وجود رؤية واضحة في المدن لتوزيع المقاسم حسب نوع الاستثمار. This study aimed to identify the four industrial estates in the Syrian Arab Republic, And knowing the size of expenditure and income for these cities, in addition to the knowledge and the number of licensed projects executed in these cities. And distribution switches between different types of industries, as well as to study the correlation between the many variables of the study. The researcher used the descriptive analytical method. It has also been studying and analyzing the data using the program spss. After analysis of the data shows decline in the number of projects implemented, the lack of correlation between most of the variables of the study, the lack of a clear vision in the cities for the distribution of plots by investment type.